O estágio supervisionado: contribuições para a formação do profissional de turismo. - Figueiredo, Maria Lúcia Brito Zabulos de (2014)
The purpose of this research project is to analyze the students' perceptions about the Supervised Internship teaching practice in the Tourism course and its contributions to training the professional with a view to Environmental Education and Sustainability (EES). It is based on authors such as Fazenda (1991), Bianchi (2004), Abdalla (2006, 2009, 2011, 2012), Pimenta (2009, 2013), and Freire (2013), in order to understand the training of the professors, the knowledge required for the educational practices and the Supervised Internship (SI) in the training of Bachelors of Tourism. And, to conceptualize sustainability and the environment, authors of the likes of Lemos (1999), Rodrigues (2000), Ruschmann (2000), Sachs (2007), and Melo (2011) were used. This is a two-stage qualitative survey, as per Lüdke and André (1986) and Bogdan and Biklan (1994). At the first stage (2nd half/2012), a questionnaire comprising open and closed questions was applied to 21 students. At the next stage (2nd half/ 2013), semi-structured interviews were conducted with six students who graduated in Tourism and, to deepen the data (1st half/2014), interviews were also made with three more. Data were analyzed and interpreted based on the content analysis technique (BARDIN, 2007; FRANCO, 2012), which allowed two dimensions of analysis to be identified: Academic training and the Supervised Internship practice. The results enabled us to identify: In the 1st dimension - academic training in Tourism - two analysis categories: 1st the challenges of training for Tourism and for Environmental Education and Sustainability (EES); and 2nd the potential of training toward the EES; and in the 2nd dimension - the Supervised Internship (SI) practice -, plus two more analysis categories: 1st internship challenges and difficulties; 2nd the potential of SI for EES. The contributions made by the SI to EES in training students taking the Tourism course were thus presented, highlighting: 1st the need for closer ties between theory and practice in the various course components aiming to strengthen these students' skills and abilities; 2nd the importance of SI providing better grounds for this theory/practice coordination, debating environmental and sustainability issues, and 3rd the valuing of an education geared by action and for action, which has in the internship the germination stage for new paradigms that can sustain and transform training, whether initial and/or continued, for these students and/or professionals working in the area.